2016
DOI: 10.2308/jeta-10511
|View full text |Cite
|
Sign up to set email alerts
|

Research Ideas for Artificial Intelligence in Auditing: The Formalization of Audit and Workforce Supplementation

Abstract: After decades of frustration with long “AI Winters,” various business industries are witnessing the arrival of AI's “Spring,” with its massive and compelling benefits. Auditing will also evolve with the application of AI. Recently, there has been a progressive evolution of technology aimed at creating “artificially intelligent” devices. Although this evolution has been permeated with false starts and exaggerated claims, there is some convergence on the fact that substantive progress has been obtained in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(147 citation statements)
references
References 38 publications
5
125
0
17
Order By: Relevance
“…Auditors through AI assisted systems can ask better questions and interact better with stakeholders, including financial officers, audit committees and company boards, thus, adding value to the audit process. This findings is akin to Issa, Sun, and Vasarhely, [7] which found that through AI visual recognition techniques, auditors are able to "understand" the content of an image taken by a drone or video captured by surveillance cameras, automatically identify the object and subject (including human faces) in the image, and subsequently organize and classify each image into a predefined logical class. Such technique can facilitate the automation of assets and inventory checks and fraud detection.…”
Section: Discussion Of Findingsmentioning
confidence: 75%
See 2 more Smart Citations
“…Auditors through AI assisted systems can ask better questions and interact better with stakeholders, including financial officers, audit committees and company boards, thus, adding value to the audit process. This findings is akin to Issa, Sun, and Vasarhely, [7] which found that through AI visual recognition techniques, auditors are able to "understand" the content of an image taken by a drone or video captured by surveillance cameras, automatically identify the object and subject (including human faces) in the image, and subsequently organize and classify each image into a predefined logical class. Such technique can facilitate the automation of assets and inventory checks and fraud detection.…”
Section: Discussion Of Findingsmentioning
confidence: 75%
“…This problem is exacerbated by the unstructured nature of Big Data and the high level of complexity and ill structureinvolved in certain audit tasks, such as the evaluation of internal controls. Hence the new methodologies can assist auditors inovercoming the aforementioned limitations.The increasing maturity of AI technologies, more specifically deep learning technology, such as visual recognition, textual analysis, natural language processing, and audio processing, provides unlimited potential and inspiration for its application to auditing [7].…”
Section: How Ai Will İnfluence the Auditing Professionmentioning
confidence: 99%
See 1 more Smart Citation
“…Big Four companies are Deloitte, PwC, KPMG and EY, the four largest auditors in the world (Statista, 2017b). As summarized by Issa, Ting, and Vasarhelyi (2017) Deloitte are introducing a contract analysis system which aims to help auditors analyse complex and long documentation provided by the audited company as audit evidence. It can be performed by text mining and natural language processing saving precious time since auditors don't necessarily have to go through each and every contract, statement and policy, the system is capable to extract the necessary information which can then be used for further investigation.…”
Section: Auditing With Artificial Intelligencementioning
confidence: 99%
“…which results in a high false positive rate. Besides, apart from the Big 4 audit firms, many auditors lack the necessary technical skills to perform such data-driven analyses on large datasets [6].…”
Section: Introductionmentioning
confidence: 99%